Intelligent carbon dioxide and lighting system for environmental monitoring / Mohammad Asyraf Ali Ahmad - Ahmad, Mohammad Asyraf Ali (2020)
This project presents the carbon dioxide monitoring system to alert the user on the carbon dioxide reading via devices. This project integrates both hardware and software to detect the level of carbon dioxide for efficient healthier lifestyle through wireless technology. Current system is impractical because the system only produces an alarm when high concentration of carbon dioxide was detected. Also, the system does not provide the user the concentration value of carbon dioxide so that user knows the concentration of carbon dioxide in their surroundings. In this work, the system consists of two main components which are MQ135 module as the input and Wi-Fi module as the switch to turn ON and OFF the sensor. The functionality of the system was tested using LED, buzzer and LCD as the output when carbon dioxide was detected and to display the reading of carbon dioxide level respectively. The three different testing area for the system was selected - residential area, construction area and main road. This system also provides a controller to control the lighting system as it could reduce the electric consumption. Internet of Thing (IoT) was embedded to the system to provide notification to user and control the lighting system.